Discrete elements and size effects. (15th February 2018) - Liu, Huai-Zhong; Lin, Jeen-Shang; He, Jiang-Da; Xie, Hong-Qiang
Highlights: Structural size effects are modeled for notched beams under tension and bending. The beams constructed with square and random packing yield similar behavior. The softening bond introduced is tied to fracture energy input and element size. The size effect law can be used in quantifying the errors from using brittle bonds. Input fracture energy may need calibration with that from structural response. Abstract: The discrete element method (DEM) in use today generally considers the bonds that bind discrete elements into a continuum to be elasto-perfectly-brittle. Such brittle bonds only give accurate failure loads for large size structures where LEFM applies. But for small to medium size structures of quasi-brittle materials such as rocks and concretes, the presence of the fracture process zone (FPZ) has significant impacts and needs to be considered. To properly model size effects, an exponential softening contact bonds model was implemented which is tied to input fracture energy and also addresses particle size issue. This was followed by a successful study of the classical size effect problems of similar edge notched beams subjected to direct tension and three-point bending. The overestimation of failure loads by brittle bonds are then addressed. The discrete nature of DEM also facilitates the use of different particle packing for structure construction, and provided insights on how FPZ evolves under sustained loading.